Therapist-guided and self-guided internet-delivered behavioural activation for adolescents with depression: a randomised feasibility trial - David Mataix-Cols; Eva Serlachius; Fabian Lenhard; Sarah Vigerland; Hanna Sahlin; Johan Åhlén; Eva Henje; Cecilia Månsson; Maria Beckman; Rebecca Andersson (BMJ Open)
Objective Access to effective treatments for adolescents with depression needs to improve. Few studies have evaluated behavioural activation (BA) for adolescent depression, and none remotely delivered BA. This study explored the feasibility and acceptability of therapist-guided and self-guided internet-delivered BA (I-BA) in preparation for a future randomised controlled trial (RCT).Design A single-blinded randomised controlled feasibility trial.Setting A specialist outpatient clinic in Sweden.Participants Thirty-two adolescents with mild-to-moderate major depression, aged 13–17 years.Interventions Ten weeks of therapist-guided I-BA or self-guided I-BA, or treatment as usual (TAU). Both versions of I-BA included parental support. TAU included referral to usual care within child and youth psychiatry or primary care.Outcomes Feasibility measures included study take-up, participant retention, acceptability, safety and satisfaction. The primary outcome measure was the blinded assessor-rated Children’s Depression Rating Scale, Revised. The primary endpoint was the 3-month follow-up.Results 154 adolescents were screened and 32 were randomised to therapist-guided I-BA (n=11), self-guided I-BA (n=10) or TAU (n=11). Participant retention was acceptable, with two drop-outs in TAU. Most participants in TAU had been offered interventions by the primary endpoint. The mean number of completed chapters (total of 8) for adolescents was 7.5 in therapist-guided I-BA and 5.4 in self-guided I-BA. No serious adverse events were recorded. Satisfaction was acceptable in both I-BA groups. Following an intent-to-treat approach, the linear mixed-effects model revealed that both therapist-guided and self-guided I-BA (Cohen’s d=2.43 and 2.23, respectively), but not TAU (Cohen’s d=0.95), showed statistically significant changes on the primary outcome measure with large within-group effect sizes.Conclusions Both therapist-guided and self-guided I-BA are acceptable and potentially efficacious treatments for adolescents with depression. It is feasible to conduct a large-scale RCT to establish the efficacy and cost-effectiveness of I-BA versus TAU.Trial registration number ClinicalTrials.gov Registry (NCT04117789).